The value of the revolving door: Political appointees and the stock market - Simon Luechinger; Christoph Moser (ETH Zurich, KOF Swiss Economic Institute, 2012)
We analyze stock market reactions to announcements of political appointments from the private sector and corporate appointments of former government officials. Using unique data on corporate affiliations and announcements of all Senate-confirmed U.S. Defense Department appointees of six administrations, we find positive abnormal returns for political appointments. These estimates are not driven by important observations, volatile stocks or industry-wide developments. Placebo events yield no effects. Effects are larger for top government positions and less anticipated announcements. We also find positive abnormal returns for corporate appointments. Our results suggest that conflicts of interest matter also in a country with strong institutions.
Keywords: G14; D73; G30; H57; 330; Political appointees; revolving door; conflict of interest; event study; stock market; Führungswechsel; Regierungswechsel; Politiker; Interessenpolitik; Börsenkurs; Rüstungsindustrie; USA